2009
DOI: 10.1152/ajprenal.90647.2008
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine stimulates the renal epithelial sodium channel by elevating cholesterol

Abstract: Cyclosporine A (CsA) is an efficient immunosuppressant used for reducing allograft rejection but with a severe side effect of causing hypertension. We hypothesize that the renal epithelial sodium channel (ENaC) may participate in CsA-induced hypertension. In the present study, we used the patch-clamp cell-attached configuration to examine whether and how CsA stimulates ENaC in A6 distal nephron cells. The data showed that CsA significantly increased ENaC open probability. Since CsA is an inhibitor of the ATP-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
46
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 48 publications
3
46
0
1
Order By: Relevance
“…We have previously shown that CsA elevates intracellular cholesterol in distal nephron cells 12 and that lovastatin antagonizes CsA-induced damage of CCD cells. 17 Therefore, this study opens a new avenue for The whole blots are shown in Supplemental Figure 3.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We have previously shown that CsA elevates intracellular cholesterol in distal nephron cells 12 and that lovastatin antagonizes CsA-induced damage of CCD cells. 17 Therefore, this study opens a new avenue for The whole blots are shown in Supplemental Figure 3.…”
Section: Discussionmentioning
confidence: 96%
“…Our recent studies suggest that CsA stimulates the epithelial sodium channel (ENaC) through elevation of intracellular cholesterol. 12 Interestingly, cholesterol inhibits Kir channels, 1 3 -1 5 including the Kir 1.1 (ROMK1) channel. 16 Therefore, CsA-induced elevation of cholesterol in CCD cells may account, at least in part, for CsA inhibition of ROMK channels.…”
mentioning
confidence: 99%
“…As described previously (24), prior to the experiments, A6 cells cultured on the polyester membrane of Snapwell inserts were thoroughly washed with NaCl solution containing 100 mM NaCl, 3.4 mM KCl, 1 mM CaCl 2 , 1 mM MgCl 2 , and 10 mM HEPES; pH was adjusted to 7.4 with NaOH. The glass micropipette was filled with NaCl solution (the pipette resistance is 7-10 megaohms).…”
Section: Methodsmentioning
confidence: 99%
“…It has also been demonstrated that cyclosporin A (CyA), an inhibitor of Ca 2+ /calmodulindependent phosphatase, calcineurin (CaN) (Hemenway & Heitman, 1999), inhibited the activity of the K + channel in both proximal tubule (Ye et al, 2006, Kubokawa et al, 2009) and principal cells of CCD (Ling & Eaton, 1993). Cyclosporin A is a a well-known immunosuppressive agent (Morris, 1981;White & Calne, 1982;Cohen, 1984), and affects various functions of the kidney other than K + channels (Epting et al, 2006;Tumlin, 1993;Grinyó & Cruzado, 2004;J. Wang et al, 2009;Damiano et al, 2010).…”
Section: +mentioning
confidence: 99%